Subset Choice Conditions and the Computation of Social Choice Sets - Fishburn, Peter C. (Quarterly Journal of Economics, 1974)
I. Subset choice conditions, 320. — II. Methods for computing C, 323. — III. Two examples, 325. — IV. Discussion, 326.